Transforming Agricultural Training Evaluation: An TERAPAN Model for Quality Vocational Education - Makmur , Andi Amal Hayat; Syahrul, Syahrul; Purnamawati, Purnamawati (International Journal of Technology and Education Research, 2025)
The effectiveness of technical training in the agricultural sector is highly dependent on the success of the overall evaluation of participants' skills. This research aims to develop a competency-based training evaluation model that can measure participants' knowledge, skills, and attitudes systematically and objectively. The study was conducted on the training of two-wheeled tractor operators at the Batangkaluku Agricultural Training Center (BBPP). With a Research and Development (R&D) approach that integrates the Borg & Gall, ADDIE, CIPP, and Logic Model models, an evaluation model called TERAPAN (Evaluative Transformation for Agricultural Training Response and Action) was produced. The model is validated through expert tests and field implementation that demonstrate high validity, practicality, and effectiveness. The results show that the TERAPAN model is able to improve the accuracy of skill measurement and provide concrete feedback to the training design. This model makes a significant contribution to strengthening the vocational agricultural training system in Indonesia, and is recommended for national adoption.